Analisis Kualitas Layanan, Persepsi Harga dan Fasilitas Pelanggan MRT Terhadap Kepuasan Pelanggan - Keisha Yudhistira; Rifaldi Faturrahman; Muhammad Fathur Rizki; Siti Sahara (Lembaga Pengembangan Kinerja Dosen, 2023)
The Jakarta Integrated Moda Raya Raya train (MRT), is one of the transportation options for the people of Jakarta in their activities. Inaugurated on March 24, 2019, several problems were complained about by passengers, namely regarding the perception of ease of transactions and customer value. Satisfaction with Perceived Ease of Transaction such as easy to learn, easy to use, clear, easy to understand, skillful, and easy to use. Satisfaction with Customer Value paid is due to added value, suitability of costs with benefits, ease of obtaining services. This research is intended for Jakarta MRT customers to have significant simultaneous satisfaction for using the Jakarta Integrated Moda Raya Train (MRT) according to Ticket Prices, Facilities and Perceptions of Ease of Transaction. Satisfaction of passengers of the Jakarta Integrated Moda Raya Train (MRT) on Perceptions of Transaction Ease and Customer Value which are jointly perceived, namely punctuality satisfaction, facility completeness satisfaction, price suitability satisfaction, departure schedule satisfaction, and function and facility satisfaction. This research was also conducted to find out how the quality of service or service, the perception of the price of MRT transportation services, and how the facilities on the MRT. Whether and how important service quality plays a role in the level of satisfaction of MRT passengers. The research method used in this research is descriptive research which is one type of quantitative research approach. This study uses a questionnaire distribution of questionnaires to 20 users or who have used MRT transportation services. In the questionnaire we provide choices about the quality of station facilities, train units, service quality, timeliness of departure, and how the fare is adjusted for MRT transportation services. In the study we found that service quality plays a very important role in the level of satisfaction of MRT passengers.